Fluid power circuits and controls : fundamentals and applications - Cundiff, John S., ....- (Boca Raton : CRC, 2002)
1 Brief Overview of Fluid Power 2 Fluid Power Basics 3 Pressure Control 4 Creating and Control of Fluid Flow 5 Rotary Actuators 6 Hydrostatic Transmissions 7 Linear Actuators 8 Temperature and Contamination Control 9 Auxiliary Components 10 Pneumatics 11 Servo Valves 12 Proportional Valves